La tecnologia della parola. Didattica inclusiva e lettura - Di Tore, Stefano (Media e tecnologie per la didattica - Open Access, 2016)
The subject of this volume are the problems related to the acquisition of instrumental literacy skills in primary school. Starting from the analysis of the results from OCSE PISA and IEA Pirls, the work relates the development of reading automatism with the trends highlighted by the two surveys; presents the didactics as the methodology for the development of reading automatism; propose a set of technological tools to support the acquisition of instrumental literacy.